2010
DOI: 10.1097/hjh.0b013e32833d4451
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal trends in cardiovascular mortality and blood pressure levels, prevalence, awareness, treatment, and control of hypertension in the Czech population from 1985 to 2007/2008

Abstract: The reduction in population blood pressure and improved hypertension control may have contributed substantially to the decrease in cardiovascular disease mortality in the Czech Republic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
46
0
13

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 23 publications
4
46
0
13
Order By: Relevance
“…Numerous randomized clinical trials in hypertensive adults have provided evidence that antihypertensive treatment reduces the risk of death and major CV events such as stroke, myocardial infarction, heart failure and renal failure and improves life expectancy (166)(167)(168)(169)(170).…”
Section: General Overviewmentioning
confidence: 99%
“…Numerous randomized clinical trials in hypertensive adults have provided evidence that antihypertensive treatment reduces the risk of death and major CV events such as stroke, myocardial infarction, heart failure and renal failure and improves life expectancy (166)(167)(168)(169)(170).…”
Section: General Overviewmentioning
confidence: 99%
“…Similar trends have been reported from many western European countries. [13][14][15][16] On the other hand, studies from South Asia have reported escalating trends in hypertension and low levels of treatment and control. 17 Only a few studies in India have evaluated hypertension awareness, treatment and control [18][19][20][21][22][23][24][25][26][27][28][29] and none was performed on a national basis.…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that approximately 25% of the US population aged 18+ suffers from the metabolic syndrome, while hypertension and diabetes mellitus affect approximately 40% and 8% of the population, respectively 1 . The treatment of metabolic syndrome is thus a great challenge in the primary prevention of ischemic heart disease (IHD).…”
Section: Introductionmentioning
confidence: 99%